The essential financial toolkit : everything you always wanted to know about finance but were afraid to ask - Estrada, Javier (Hampshire, England Palgrave MacMillan, 2006)
Math and jargon make essential financial concepts seem intimidating, but that is simply because most books do not have the goal of being accessible to interested readers -- this book does. In ten easy-to-read chapters, it explains all the essential financial tools and concepts, fully illustrated with real-world examples and Excel implementations.
Tool 1: Returns Tool 2: Mean Returns Tool 3: Risk: Standard Deviation and Beta Tool 4: Diversification and Correlation Tool 5: Required Returns and the CAPM Tool 6: Downside risk Tool 7: Risk-Adjusted Returns Tool 8: NPV and IRR Tool 9: Multiples Tool 10: Bonds Appendix: Some Useful Excel Commands
Keywords: Empresas -- Finanzas; Libros electrónicos